Immunophenotyping Pattern in Childhood Acute Leukemia in the Adam Malik Hospital Medan - Putri Chadijah Tampubolon; Bidasari Lubis; Adi Koesoema Aman; Malayana R Nasution (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
Leukemia is the most common malignancy at the age of under 15 years, with a ratio of 1 to 3 cancer cases in children.Immunophenotyping will improve accuracy and easily provide data reproducibility. To determine the immunophenotypingpattern in patients with acute leukemia in the Pediatric Center at the Adam Malik General Hospital, Medan. This research wasa cross-sectional study in children suffering from acute leukemia in the Pediatric Unit Adam Malik General Hospital, Medanbased on CBC, peripheral smear, bone marrow morphology, and flow cytometry immunophenotyping. Samples wereevaluated for blast morphologic and immunophenotyping was carried out. Results of morphologic observation andimmunophenotyping were compared. From 20 samples using the monoclonal antibody with flow cytometryimmunophenotyping, concordance with morphology is good (κ = 0.886). After classification, the percentage of acuteleukemia was 45% B-ALL, 35% AML, and 20% T-ALL. One of 10 samples morphologically classified as ALL but reported asAML. Immunophenotyping has been shown to increase diagnostic accuracy and assist in establishing lines in blast cells,which was initially merely based on morphological features.